Hubungan Antara Persepsi Terhadap Insentif Dengan Intensi Turnover Karyawan - Purnomo, Astika Rangga Dwi, Drs. Muh. Amir, M.Si (2015)
The existence of distrust of employees of the company, where the performance is not too much attention. Employee performance received less attention in terms of finances. In fact, every company needs employees with a forward thinking and good performance for the company's progress. The aim of this study was to determine: 1) To determine whether there is correlation between perceptions of incentives with turnover intention of employees; 2) To find out how much impact the perceptions of incentives with turnover intention of employees; 3) To determine the level of perception to employee incentives; 4) To determine the level of employee turnover intention. Population of this research are employees of the company Batik Winda Sari were 70 active employees. Based on the number of the population research institute, using the whole population. The necessary data obtained through the questionnaire perceptions of incentive and turnover intention karyawan.Teknik data analysis used is product moment analysis, which previously carried the assumption of normality and linearity test. Results of this study were: 1) Both variables showed a significant negative correlation between perceptions of incentives with the intention turnoverkaryawan, with the magnitude of the correlation coefficient -0.382, p = 0.001 (p <0.01); 2) The magnitude of the impact of perceptions of incentives with turnover intention of employees is 14.6% because there are still 85.4%, which affects turnover intention. For example: feel not respected, compensation is not enough, feel the time off is not enough, change management, machinery and office equipment were outdated, unrealistic targets, lack of support (Ramadhyaz, 2012); 3) Perceptions of employees on the subject of incentives is high; and 4) Intention turnover on the subject is low.